Circular RNA PRKCI (hsa_circ_0067934): a potential target in the pathogenesis of human malignancies - Qiu, Shipei; Zhang, Kefan; Chen, Siyu; Yin, Shuting (Frontiers in Oncology, 2024)
Circular RNAs (circRNAs) are a new type of endogenous non-coding RNA formed by a covalent closed loop. CircRNAs are characterized by specificity, universality, conservation, and stability. They are abundant in eukaryotic cells and have biological regulatory roles at various transcriptional and post-transcriptional levels. The upregulation of circPRKCI has been observed in a variety of tumors and is directly related to the clinicopathological characteristics of tumors and prognosis. More importantly, circPRKCI can participate in the tumorigenesis, progression, recurrence, and metastasis of various tumors through many functional mechanisms, including the activation of signaling pathways, such as the phosphatidylinositol-3-kinase (PI3K)/AKT pathway, and sponging of many microRNAs (miRNAs). This review summarizes the progress achieved in understanding the biological functions of circRNA PRKCI in various tumors. The goal is to inform the discovery of more functional mechanisms and new anticancer molecular targets.